Inclusive Online Nursing Education: Learner Perceptions of Universal Design for Learning Approaches - Ann Celestini; Agniewszka (Aga) Palalas (Canadian Journal for the Scholarship of Teaching and Learning)
Diversity in age, background, circumstances, and abilities among post-secondary learners has become increasingly common in online nursing education. Thus, there is a need for educators to build an inclusive environment that is responsive to this variety, to optimize learner achievement.  Universal Design for Learning (UDL) offers educators a theoretical framework to proactively design an inclusive online course curriculum that is responsive to varied learner populations and minimizes learning barriers encountered. A convergent mixed-methods descriptive case study was conducted of learners enrolled in a large first-year undergraduate nursing course in Canada, which was redesigned using UDL principles. The purpose of this case study was to answer the research question: How do learners’ rate and describe the effectiveness of instructional strategies used in supporting inclusivity of diverse learning preferences and needs in an online environment. Data was collected in 2020, from a cohort of 230 learners using a survey questionnaire (n=40) and focus group (n=7) by a hired research assistant, for the convergent mixed-methods analysis and resulting discussion. Survey respondents rated accessible course material, inclusive lecture strategies, accommodations, inclusive assessment, and classroom constructs of the survey tool, as being most inclusive of diverse needs. Focus group participants described assessment methods, instructor presence, and UDL based course design elements, as the preferred instructional strategies used in the curriculum, with group work and navigation issues being most problematic. A purposeful selection of synchronous and asynchronous UDL based instructional strategies by educators, which integrate multiple means of engagement, representation, action and expression, offered an inclusive online environment for diverse learning needs.